Secondary structure investigation of bovine serum albumin (BSA) by Fourier transform infrared (FTIR) spectroscopy in the amide III region - Li, Dongmin; Zhang, Hong; Ma, Gang (European Journal of Chemistry, 2014)
Fourier transform infrared spectroscopy is widely used to analyze protein secondary structures. The common strategy in this field is to analyze the conformation sensitive 1700-1600 cm-1 amide I region of protein FTIR spectrum. Though the amide III region of protein is also sensitive to secondary structural changes, its potential for protein secondary structural analysis is largely unexplored. In this paper, we performed a detailed investigation on the second structural analysis of bovine serum albumin by monitoring the spectral variation of the amide III band under a variety of pH conditions by FTIR spectroscopy and FTIR second derivative spectroscopy. Our results show that both acidic and basic conditions have pronounced effects on the overall secondary structures of BSA, suggesting denaturation effects. Furthermore, we observe that the amide III band profiles under acidic and basic conditions appear to be quite different. Our results clearly demonstrate that the amide III region is a promising probing region for protein secondary structural analysis.